Application of Omics Technologies for Evaluation of Antibacterial Mechanisms of Action of Plant-Derived Products - Santos, Bruno S. dos; Silva, Luís C. N. da; Silva, Túlio D. da; Rodrigues, João F. S.; Grisotto, Marcos A. G.; Correia, Maria T. dos Santos; Napoleão, Thiago H.; Silva, Márcia V. da; Paiva, Patrícia M. G. (Frontiers in Microbiology, 2016)
In the face of increasing bacterial resistance to antibiotics currently in use, the search for new antimicrobial agents has received a boost in recent years, with natural products playing an important role in this field. In fact, several methods have been proposed to investigate the antibacterial activities of natural products. However, given that the ultimate aim is future therapeutic use as novel drugs, it is extremely necessary to elucidate their modes of action, stating the molecular effects in detail and identifying their targets in the bacterial cell. This review analyzes the application of “omics technologies” to understand the antibacterial mechanisms of bioactive natural products, to stimulate research interest in this area and promote scientific collaborations. Some studies have been specifically highlighted herein by examining their procedures and results (targeted proteins and metabolic pathways). These approaches have the potential to provide new insights into our comprehension of antimicrobial resistance/susceptibility, creating new perspectives for the struggle against bacteria, and leading to the development of novel products in the future.